EVALUASI IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM MENGATASI KEMISKINAN MASYARAKAT NELAYAN (STUDI KASUS NELAYAN TRADISIONAL DESA BENDAR, KECAMATAN JUWANA, KABUPATEN PATI) - Diah Meitasari; Budi Setiyono; Achmad Taufiq (Journal of Politic and Government Studies, 2015)
Poverty in Indonesia, one of them comes from fishery sector because the fishermen are minimal in the fulfillment of clothes, foods, shelters, health and education altough Indonesia has a total sea area of about 3.544 million km2 and has a huge potential for fisheries. The Ministry of Maritime Affairs may overcome the poverty in fishery sector through the developing of Program Usaha Mina Perdesaan (PUMP). Therefore, the formulation of the problem in this research is